The Publishing and Review of Reference Sources, 1st edition Bill Katz, Robin Kinder - Katz, Bill (Routledge, 2020)
This book, first published in 1987, provides important information on reference publishing, including valuable guidelines on evaluating publications and sources. The articles contained here are all written by leading experts in the field.